(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The study was performed to determine the level of knowledge, attitude, and practice among different professionals toward zoonotic diseases in selected coastal areas of Barguna district, Bangladesh. Materials and Methods: A total of 485 respondents were randomly selected from different upazilas (sub-districts) of Barguna district, Bangladesh. A questionnaire-based survey was conducted to collect data about awareness of zoonosis, hygienic management, zoonotic disease transmission from different species of domestic animals and consumption of their products, consciousness on management of pet animals, disease transmission from wild animals, effects of natural disaster on zoonosis, and extension works on zoonosis provided by government or private sector. Results: Based on the level of knowledge of the different respondents, meat (43.92%) is the prime way for transmission of zoonotic disease followed by egg (18.14%) and milk (13.61%). The awareness regarding management of pet animals (23.71%) and zoonotic disease from wild animals (26.69%) were more or less similar. It has been observed that 33.81% respondents were conscious about natural disaster causing zoonotic infection. The respondents also mentioned that extension services about zoonotic infection provided by government or private sector was 34.22%. Among all the respondents, the awareness of zoonotic infection was high in employee of livestock department followed by employee of health department and teachers. Conclusion: The awareness of zoonoses was high in employee of livestock department followed by the employee of health department, teachers, and other professionals. The present study observed that low educational background of professionals or non-health educated professionals is not conscious on zoonotic diseases. Further work should be taken to assess the prevention and control strategies regarding zoonosis in study area. J. Adv. Vet. Anim. Res., 6(3): 284-289, September 2019